Correction: Zhu et al. Investigation on the Welding Residual Stress Distribution in Multi-Segment Conical Egg-Shaped Shell. J. Mar. Sci. Eng. 2025, 13, 578 - Yongmei Zhu; Ao Sun; Longbo Zhou; Lihui Wang; Xilu Zhao (Journal of Marine Science and Engineering)
In the original publication, there was an error in the order of author names as published [...]